2024
DOI: 10.1002/jcsm.13412
|View full text |Cite
|
Sign up to set email alerts
|

The burden of frailty in heart failure: Prevalence, impacts on clinical outcomes and the role of heart failure medications

Hsi‐Yu Lai,
Shih‐Tsung Huang,
Stefan D. Anker
et al.

Abstract: BackgroundFrailty often coexists with heart failure (HF), which significantly aggravates the clinical outcomes of older adults. However, studies investigating the interplay between frailty and HF in older adults are scarce. We aimed to assess the prevalence of frailty using the cumulative deficit approach and evaluate the impacts of frailty on health utilization, use of HF‐related medications and adverse clinical outcomes (all‐cause mortality, all‐cause readmissions and HF readmissions) among older HF patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The majority of their patients were treated with beta-blockers and RAS inhibitors, as well as diuretics. They also showed that HF medication was reduced after discharge [ 12 ]. Another study by Qin X et al showed that the discontinuation of RAS inhibitors and beta-blockers after discharge was common and the long-term adherence to HF medications was suboptimal [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of their patients were treated with beta-blockers and RAS inhibitors, as well as diuretics. They also showed that HF medication was reduced after discharge [ 12 ]. Another study by Qin X et al showed that the discontinuation of RAS inhibitors and beta-blockers after discharge was common and the long-term adherence to HF medications was suboptimal [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to the fit group, the severe frailty group exhibited a higher risk of all-cause mortality (adjusted HR = 1.16, 95% CI = 1.11-1.21), all-cause readmissions [subdistributional hazard ratio (sHR) = 1.21, 95% CI = 1.16-1.25], and HF-related readmissions (sHR = 1.14, 95% CI = 1.09-1.20) at the two-year follow-up. The study concluded that frailty is highly prevalent among older HF patients and is associated with an increased risk of all-cause mortality, all-cause readmissions, and HF readmissions [10].…”
Section: Introductionmentioning
confidence: 95%